I, too, sing America the story of Langston Hughes - Rhynes, Martha E. (Greensboro, N.C. : Morgan Reynolds, 2002)
A biography of a man who, from the 1920s Harlem Renaissance through the 1960s, wrote poems, stories, and books which celebrated his African American heritage.
Nobody loves a genius child -- Adrift on the big sea of life -- Lion of Lincoln and Godmother Mason -- Wandering and wondering -- Homeless, but not friendless -- Jesse B. Semple confronts Jim Crow -- Were you ever a member of the Communist party? -- Proud spokesman -- Walls come a 'tumblin' down -- Timeline -- Sources -- Glossary -- Major works -- Bibliography -- Websites -- Index.
Includes bibliographical references and index
12 - 16 years
Keywords: Hughes, Langston -- 1902-1967; Hughes, Langston -- 1902-1967.; Poets, American -- 20th century -- Biography -- Juvenile Literature; African American poets -- Biography -- Juvenile Literature; Poets, American; African Americans; American poets